The potential of TerraSAR-X to observe wind wave interaction at the ice edge - Gebhardt, Claus; Bidlot, Jean Raymond; Jacobsen, Sven; Lehner, Susanne; Persson, P. Ola G.; Pleskachevsky, Andrey L. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2017)
This paper performs a study on sea state and wind fields at the ice edge boundary by utilizing information from different sources including synthetic aperture radar (SAR) satellite imagery, weather and sea state analyses from the European Centre for Medium-Range Weather Forecasts, shipborne in-situ measurements, and AMSR2 ice charts. The basis is a Stripmap scene from the TerraSAR-X satellite acquired on October 18, 2015, at ∼18 UTC, in support of the cruise of the research vessel R/V Sikuliaq in the Beaufort/Chukchi Sea. This scene covers an area with a length of more than 100km and comprises both the marginal ice zone and, for the largest part, open water. The wave and windfieldisretrieved from satellite at high spatial resolution using empirical retrieval algorithms. These algorithms are XWAVE and XMOD-2 specifically developed for X-Band SAR. XWAVE allows for determining the significant wave height not only for long swell waves, but also for short waves with their wave pattern being hardly visible from SAR. The latter is based on the analysis of image spectrum parameters and spectral noise. As well, the possibility of the imaging quality of longer waves visible from SAR being affected by SAR-specific nonlinear imaging effects is narrowed down. Both the wave and wind field are found to exhibit considerable spatial variability, and their relationship is analyzed. The relevance of the findings of this study with respect to wave/ice modeling is discussed.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Arctic marginal seas; Marginal ice zone (miz); Sea state; TerraSAR-X; Wind